2018
DOI: 10.26451/abc.05.02.04.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tremulation display in male agonistic behavior of the black-eyed leaf frog (Agalychnis moreletii: Hylidae).

Abstract: -The black-eyed leaf frog (Agalychnis moreletii) is a critically endangered hylid frog restricted to humid lowland and lower montane forests of southern Mexico and northern Central America. Very few reports exist on wild reproductive behavior of this species. Lower body tremulation display has been reported as a relevant part of agonistic interactions between males of the related species A. callidryas but has never been reported in other species of Agalychnis. Herein, we present the first report and descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…He described the chuckle call as having 3-5 notes, with duration of 0.35 s, and dominant frequency of 1,285 Hz and the "soft tlock call" as a single note of 0.028 s duration and mean dominant frequency of 1,565 Hz. As in A. callidryas, males of A. moreletii use tremulation displays and aggressive chuckle calls during agonistic interactions that might be important to defend territories or calling sites (Serrano et al, 2018). In A. saltator, Roberts (1994) reported that during breeding aggregations males produced a "soft squeaking and chuckling noise" that differed from the advertisement call.…”
Section: Discussionmentioning
confidence: 99%
“…He described the chuckle call as having 3-5 notes, with duration of 0.35 s, and dominant frequency of 1,285 Hz and the "soft tlock call" as a single note of 0.028 s duration and mean dominant frequency of 1,565 Hz. As in A. callidryas, males of A. moreletii use tremulation displays and aggressive chuckle calls during agonistic interactions that might be important to defend territories or calling sites (Serrano et al, 2018). In A. saltator, Roberts (1994) reported that during breeding aggregations males produced a "soft squeaking and chuckling noise" that differed from the advertisement call.…”
Section: Discussionmentioning
confidence: 99%